Pengaruh Pelatihan dan Motivasi Terhadap Kinerja Pegawai (Studi Pada Badan Pengelolaan Keuangan Dan Pendapatan Daerah Kota Banjar) - Hilda Kesumawaty (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The background of this research is that the performance of the employees of the Financial Management Agency and Regional Income Management in the City of Banjar has not been maximized due to the lack of training, one of which is asset management and service delivery by employees who tend to be less focused and slow resulting in organizational plans or targets not running optimally because of the cycle time is not quite right. The formulation of the problem posed in this study is as follows: 1. What is the effect of training on employee performance? 2. How does work motivation affect employee performance? 3. What is the influence of training and work motivation simultaneously on employee performance at the BPKPD in Banjar City? The research method used is quantitative. Data collection techniques through questionnaires, literature, and documentation. With a research sample of 50 employee respondents and data analysis used through statistical tests of correlation and multiple regression using SPSS version 26.00 for windows. The research results show: 1). Training tends to be good and employee performance is high, so training has a positive and significant effect on employee performance. This means that the better the training, the better the performance of employees at the Banjar City Regional Revenue and Financial Management Agency. 2). Work motivation tends to be high and employee performance is high, so work motivation has a positive and significant effect on employee performance. This means that the higher the employee's work motivation, the higher the employee's performance at the Banjar City Regional Revenue and Financial Management Agency. 3). Training and work motivation tend to be good and employee performance is high, so training and work motivation have a positive and significant effect on employee performance. This means that the better the training and the higher the work motivation, the better the performance of employees at the Banjar City Regional Revenue and Financial Management Agency.